2006
DOI: 10.1124/jpet.106.108803
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Mediates Angiotensin-Converting Enzyme Inhibitor-Induced Angiogenesis in Coronary Endothelium

Abstract: The beneficial effect exerted by angiotensin-converting enzyme inhibitors (ACEI) on vascular endothelium has been attributed to restoration of endothelial cell survival properties and improvement of angiogenesis. Fibroblast growth factor (FGF)-2 is an angiogenic factor for the microvascular endothelium, which tonically promotes endothelial cell growth and survival through an autocrine/ paracrine mechanism. Here, we formulate the hypothesis that FGF-2 might contribute to the prosurvival/proangiogenic effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…For example, ACE inhibitor treatment improves endothelial function in septic patients (71) or in rabbits with lipopolysaccharide-induced endotoxic shock by an NO-dependent mechanism (72). ACE inhibitors also promote angiogenesis in an NO-dependent manner that results from B1R activation (73).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ACE inhibitor treatment improves endothelial function in septic patients (71) or in rabbits with lipopolysaccharide-induced endotoxic shock by an NO-dependent mechanism (72). ACE inhibitors also promote angiogenesis in an NO-dependent manner that results from B1R activation (73).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudocapillary sprouting from vessel rings of the human umbilical artery and characterization of the cells present in the pseudocapillaries were evaluated as described previously (Donnini et al, 2006). Cell Cultures.…”
Section: Methodsmentioning
confidence: 99%
“…We resuspended 1000 cells per well (of a 96-well multiplate) in 10% CS, and after cell adherence (3-4 h), we replaced the supernatant with medium containing ACEI (0.01-10 M) and 0.1% CS. Cells were kept in culture for 5 consecutive days, and medium with test substances was added freshly at 36 and 72 h. Cells were then fixed, stained, and randomly counted at 10ϫ magnification (Donnini et al, 2006). Cell survival in response to ACEI was also assessed by the MTT test (Pezzatini et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE inhibitors are widely used as antihypertensive drugs. Recently, studies reported the beneficial effects of ACE inhibitors on tumor growth by inhibiting neovascularization 27,28 and in myocardial ischemia by improving angiogenesis 29 . In this study, we found that enalapril increased angiogenesis in diabetic and diabetic hind limb ischemic rats.…”
Section: Discussionmentioning
confidence: 99%